Fast Response Estimation of Passively Controlled Structures Using Artificial Intelligence - Al Houri, Ausamah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The research on the applicability of using passive control systems as a seismic mitigation approach and energy dissipating devices has grown significantly in the past decades with the focus on investigating the seismic response of the structure equipped with viscous dampers. In general, viscous damper as a device can be utilized for retrofitting and rehabilitating of old buildings, in addition, to optimize the cost of the new ones. When used in a structure, these structural dissipating devices can enhance the energy absorption capacity of the building under shaking intensities resulting in decreased displacements and acceleration responses. Current analysis approaches for finding a safe and optimized design is considered to be time and effort consuming since it requires several trial and errors to achieve the targeted responses. Nowadays, the literature is full with many high reliable estimation methods, such as artificial neural networks, that can be used to define a mathematical prediction model based on certain input parameters to reduce the need for doing a long trial and errors. Therefore, the main objective of this study is to get benefit from these available estimation methods to propose a prediction models using ANN to obtain the response of structures equipped with viscous dampers from the behavior of the bare building. As a part of the study, thousands of numerical analyses by means of nonlinear response history analysis (direct integration method) are performed in order to estimate the response of various designs of bare and controlled reinforced concrete (RC) structures under different real earthquake records. Thereafter, the outputs of the numerical analyses will be used as an input for defining the coefficients of the estimation models using artificial neural networks (Levenberg-Marquardt backpropagation method) that will be proposed in this study. The proposed estimation models require one-fourth of the time to build the model and determine the results in comparison to NTHA which results in faster, minimized cost and effort approach. In addition to that, the proposed prediction models exhibited high performance and accurateness in estimating the responses of RC structures. Keywords: Reinforced concrete, optimization of dampers, damping, energy dissipation, artificial intelligence, estimation models, nonlinear response history analysis.

ÖZ: Pasif kontrol sistemlerinin bir sismik yük azaltma yaklaşımı ve enerji sönümleme cihazları olarak kullanılmasının uygulanabilirliği üzerine yapılan araştırmalar, viskoz damperlerle donatılmış yapının sismik tepkisinin araştırılmasına odaklanılarak son yıllarda önemli ölçüde artmıştır. Genel olarak, bir cihaz olarak viskoz damper, yeni uygulamarın maliyetini optimize etmek için ek olarak eski binaların güçlendirilmesi ve rehabilitasyonu için kullanılabilir. Bir yapıda kullanıldığında, bu elemanlar, sarsıntı yoğunlukları altında binanın enerji sönümleme kapasitesini artırabilir ve bu da yer değiştirmelerin ve hızlanma tepkilerinin azalmasına neden olur. Güvenli ve optimize edilmiş bir tasarım bulmak için mevcut analiz yaklaşımları, hedeflenen yanıtlara ulaşmak için birçok deneme ve hata içerdiğinden, zaman ve çaba gerektiren olarak kabul edilir. Günümüzde literatür, uzun bir deneme ve hata oranını azaltmak için belirli girdi parametrelerine dayalı bir matematiksel tahmin modelini tanımlamak için kullanılabilen yapay sinir ağları gibi birçok yüksek güvenilirlikli tahmin yöntemiyle doludur. Bu nedenle, bu çalışmanın temel amacı, sade (kontrolsüz) binanın davranışından, viskoz sönümleyicilerle donatılmış yapıların tepkisini elde etmek için yapay sinir ağını kullanan bir tahmin modelleri önermek için bu mevcut tahmin yöntemlerinden yararlanmaktır. Çalışmanın bir parçası olarak, sade (kontrolsüz) ve kontrollü betonarme yapıların çeşitli tasarımlarının farklı gerçek deprem kayıtları altındaki tepkisini tahmin etmek için doğrusal olmayan davranış geçmişi analizi (doğrudan integrasyon yöntemi) aracılığıyla binlerce sayısal analiz yapılacaktır. Bundan sonra sayısal analizlerin çıktıları, bu çalışmada önerilecek tahmin modellerinin katsayılarının tanımlanmasında girdi olarak kullanılacaktır. Anahtar Kelimeler: Betonarme, sönümleyicilerin optimizasyonu, sönümleme, enerji sönümleme, yapay zeka, tahmin modelleri, doğrusal olmayan tepki geçmişi analizi.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Asst. Prof. Dr. Umut Yıldırım.
Keywords: Civil Engineering; Seismic Design; Buildings - Earthquake effects--Earthquake resistant design; Buildings, Reinforced concrete; Reinforced concrete; optimization of dampers; damping; energy dissipation; artificial intelligence; estimation models; nonlinear response history analysis